Local Branding in Rural Development: Entrepreneurs' Perspective - Patrycja BRAŃKA (Communications of International Proceedings, 2025)
Specific endogenous resources of rural areas and their spatial diversity create great opportunities for implementing local brands. Local brands as signs that distinguish products and services of a given territory are an expression of joint efforts and aspirations of local communities to promote their heritage. Implementing a local brand can have a significant impact on the socio-economic development of the area. The aim of the article has been to identify the opinions of entrepreneurs on the role that a local brand can play and the barriers to its implementation in the light of the concept of  territorial capital. There are many studies on the problem of local brand, regarding the factors that determine the success of its implementation. The author's intention is to verify the theory with the opinions of entrepreneurs operating in the Ojców National Park (ONP) and its surroundings. The ONP is located in an attractive area in terms of geography, nature and culture, where various local products and services are offered, but a local brand has not been developed so far. To answer such a research question a survey among entrepreneurs operating in the Ojców National Park and its surroundings has been conducted. All entrepreneurs are producers of local products and services (mainly for tourists). The results of the research clearly showed that the studied area is attractive enough in terms of tourism as well as it has the potential for local products and services, and a local brand would be an effective promotion tool. It would also would contribute to the development of the tourist offer and thus increase tourist traffic on weekdays and in the autumn-winter period. The most evident barrier to the implementation of a local brand is insufficient cooperation between the Park authorities and entrepreneurs, as well as between entrepreneurs themselves. The lack of such cooperation could be primarily visible in the difficulties of integrating a common offer for products and services as well as joint promotion of the brand. The article highlights the concept of territorial capital as a sine qua non condition for effective brand implementation. Territorial capital is created by both endogenous resources and the willingness and ability of communities to cooperate around various development goals. The results of the conducted research have led to the conclusion that, despite the existence of attractive endogenous resources in the analyzed area, the cooperation skills of the local entities are insufficient. This fact  makes it difficult or even impossible to introduce a local brand.
Keywords: local brand; rural areas; territorial capital; territorial development; entrepreneurship in rural areas